Digital Financial Compliance Challenges: Applying Routine Activity Theory to Online Gambling Networks Analysis - Rizal Mawardi; Vira Nuraeni; Jasman Jasman; Huda Trihatmoko; Fangky A. Sorongan; Septian Aripin; Syaefulloh Maulana Malik (Ital Publication, 2026)
This study examines Indonesia's Financial Intelligence Unit (INTRAC)